离心式无损密封结构设计 - 曹海军 (Jixie chuandong)
A centrifugal nondestructive sealing structure is designed.The seal of the relative motion position of the mechanical rotary structure is realized by the characteristic,the centrifugal is bigger than gravity when the sealing medium rotated with sealing cover and oil ring in a high speed enters into seal gap.The problems of wear and oil leakage of the common sealing method are solved.